2012
DOI: 10.1111/j.1365-294x.2012.05601.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation shapes genetic novelty in a globally important invader

Abstract: Acacia saligna is a species complex that has become invasive in a number of countries worldwide where it has caused substantial environmental and economic impacts. Understanding genetic and other factors contributing to its success may allow managers to limit future invasions of closely related species. We used three molecular markers to compare the introduced range (South Africa) to the native range (Western Australia). Nuclear markers showed that invasive populations are divergent from native populations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 66 publications
0
52
0
Order By: Relevance
“…However, A. senegal had a higher and significant genetic differentiation among populations (F ST = 0.100), probably due to the fact that it is native. A. saligna and A. pycnantha native (Australian) populations revealed higher genetic differentiation (F ST = 0.330) compared to the invasive (South African) range (F ST = 0.132) (Thompson et al, 2012). Still, invasive A. saligna demonstrates greater differentiation than A. longifolia.…”
Section: Genetic Diversity and Population Differentiationmentioning
confidence: 94%
See 1 more Smart Citation
“…However, A. senegal had a higher and significant genetic differentiation among populations (F ST = 0.100), probably due to the fact that it is native. A. saligna and A. pycnantha native (Australian) populations revealed higher genetic differentiation (F ST = 0.330) compared to the invasive (South African) range (F ST = 0.132) (Thompson et al, 2012). Still, invasive A. saligna demonstrates greater differentiation than A. longifolia.…”
Section: Genetic Diversity and Population Differentiationmentioning
confidence: 94%
“…Many molecular markers have been used in population and phylogenetic studies in acacias, including inter-simple sequence repeats (ISSRs), simple sequence repeats (SSRs or microsatellites), chloroplastidial DNA and internal and external transcribed spacers (ITS and ETS respectively) (Thompson et al, 2012(Thompson et al, , 2015Omondi et al, 2010Omondi et al, , 2016Harris et al, 2012;Miller et al, 2011;Le Roux et al, 2011Fredua-Agyeman et al, 2008;Mulumba et al, 2012;Josiah et al, 2008;Ndlovu et al, 2013;Murphy et al, 2010;Brown et al, , 2012. Furthermore, several SSRs markers have been developed for Acacia species, such as A. atkinsiana (Levy et al, 2014), A. brevispica (Otero-Arnaiz, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…First, propagule pressure mitigates the impact of demographic stochasticity; second, increased genetic and phenotypic variation improves the chances of successful colonization (Colautti et al 2006;Simberloff 2009;Rius and Darling 2014). A recent meta-analysis, which controlled for the effects of population size, found strong evidence that higher levels of genotypic and phenotypic diversity in founder groups increased establishment success (Forsman 2014 Thompson et al 2012;Rius and Darling 2014).…”
Section: Colonization and Establishment: Genetic Diversitymentioning
confidence: 99%
“…Studies have revealed significant information regarding genetic variation, population differentiation, and introduction history of a few invasive species using molecular markers (Chun et al 2010, Thompson et al 2012, Vardien et al 2013. Few studies have also attempted to explore range expansion of L. camara in different countries (Vardien et al 2012, Ray andQuader 2014).…”
Section: Understanding the Species Complexmentioning
confidence: 99%